Leukotriene B4 production in healthy subjects carrying variants of the arachidonate 5-lipoxygenase-activating protein gene associated with a risk of myocardial infarction - Maznyczka, Annette; Mangino, Massimo; Whittaker, Andrew; Braund, Peter; Palmer, Tom; Tobin, Martin; Goodall, Alison H.; Bradding, Peter; Samani, Nilesh J. (Clinical science (1979), 2007)
Leukotrienes are implicated in the pathogenesis of coronary artery disease. Recently two haplotypes (HapA and HapB) in the gene encoding ALOX5AP (arachidonate 5-lipoxygenase-activating protein), the main regulator of 5-lipoxygenase, have been associated with a doubling of the risk of myocardial infarction. Studies have also shown that treatment with a leukotriene inhibitor reduces biomarkers of coronary risk in patients carrying HapA, raising the possibility of developing genotype-specific therapy. In the present study, we examined whether carriage of HapA or HapB is associated with increased LTB4 (leukotriene B4) production in healthy subjects. Age- and gender-matched healthy HapA carriers (n=21), HapB carriers (n=20) and non-A/non-B carriers (n=18), with no reported history of cardiovascular disease, were recruited following DNA screening of 1268 subjects from a population-based study. Blood neutrophils were isolated, and LTB4 production was measured in response to stimulation with 1 μmol/l of the calcium ionophore A23187. There was no difference in the mean level for LTB4 production in the three groups (non-A/non-B, 24.9±8.3 ng/106 cells; HapA, 22.2±11.9 ng/106 cells; HapB, 19.8±4.8 ng/106; P=0.14). The findings indicate that if either the HapA or the HapB haplotype of ALOX5AP indeed increases cardiovascular risk, then the mechanism is not simply due to a systematically observable effect of the haplotype on LTB4 production in response to stimulation. The results suggest that knowledge of a patient's haplotype may not provide useful information on the probable clinical response to ALOX5AP inhibitors.